2019
DOI: 10.1101/784991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prefrontal High Gamma in ECoG tags periodicity of musical rhythms in perception and imagination

Abstract: Rhythmic auditory stimuli are known to elicit matching activity patterns in neural populations. Furthermore, recent research has established the particular importance of highgamma brain activity in auditory processing. Here, we use electrocorticography (ECog) recordings of nine participants, to see whether high-gamma activity tracks the envelope of musical rhythms during rhythm perception and imagination. Rhythm imagination was elicited by asking the participants to imagine the rhythm to continue during pauses… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Rather, these neural signals can be used as a powerful complement to behavioural responses (offering several advantages owing to little reliance on decisional processes and movement abilities). Moreover, when recorded intracranially, field potentials can offer critical insights into the spatio-temporal characteristics of the neural network involved in meter processing ([ 72 , 77 ], see also [ 78 ]).…”
Section: Approaches To Measure Internal Representation Of Metermentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, these neural signals can be used as a powerful complement to behavioural responses (offering several advantages owing to little reliance on decisional processes and movement abilities). Moreover, when recorded intracranially, field potentials can offer critical insights into the spatio-temporal characteristics of the neural network involved in meter processing ([ 72 , 77 ], see also [ 78 ]).…”
Section: Approaches To Measure Internal Representation Of Metermentioning
confidence: 99%
“…However, these measures might be less sensitive to fine temporal regularity (see the electronic supplementary material, figure S4). Finally, a third family of measures include autocorrelation (based on high self-similarity of a periodic signal when shifted by time equivalent to the pulse period) ([ 72 ]; see the electronic supplementary material, figures S4 and S5) and frequency-tagging (based on the fact that periodic recurrence in a signal can be identified in the frequency domain as narrow-band peaks of energy centred at the frequencies corresponding to the pulse period and its harmonics) [ 29 , 81 ].…”
Section: Approaches To Measure Internal Representation Of Metermentioning
confidence: 99%
“…Isochronous rhythms, and the meters they induce, have been widely studied in sensorimotor synchronization tasks (typically assessed by tapping experiments), which have found that participants typically tap a little early (for non-musicians, approximately 20-80 ms before the auditory cue, Aschersleben, 2002), and that mechanisms related to adaptation (period and phase correction) and anticipation (extrapolation and perseveration) are used by performers to synchronize with each other and with gradually changing or tempos (Harry & Keller, 2019). Furthermore, the top-down aspect of meter perception is nicely demonstrated by how the frequency content of neural responses of rhythms depend on the meter the participant is asked to imagine while listening to isochronous pulses (Nozaradan et al, 2012), and how periodicities are preserved in high-gamma brain signals when a previously heard rhythm is imagined (Herff et al, 2020).…”
mentioning
confidence: 99%
“…Neural entrainment to pulses within complex rhythms have shown to occur in the auditory and motor cortices linking to temporal expectancy and, attentional and movement coordination (Large, Herrera, & Velasco, 2015;Large & Snyder, 2009). This continues to be true even when rhythms are only imaginarily anticipated rather than auditorily sensed (Herff, et al, 2020).…”
Section: Neural Entrainmentmentioning
confidence: 98%
“…When listening to music, tempo is spontaneously and uniquely processed by the cognitive system. Listeners can mentally represent a rhythmic cycle of a stimuli with a steady isochronous pulse and tease apart the various accents in a metric representation (Herff, et al, 2020). For example, strong accenting beats have shown greater discrimination in cognitive processing generating greater attention around cyclic pitches and notes, conforming to regularities (Fujioka, Trainor, Large, & Ross, 2009;Jones M. R., 1987).…”
Section: Chapter 1 Background Introductionmentioning
confidence: 99%